Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate - García-Plazaola, J. I.; FARIA, T.; Abadía, J.; Chaves, M. M.; Pereira, J. S. (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.166710.1093/jxb/48.9.1667
Keywords: chlorophyll fluorescence; pigments; Quercus suber; thermal dissipation; xanthophylls